Influence of social media and online reviews on university students' purchasing decisions. (15th February 2022) - Torabi, Mostafa; Bélanger, Charles H.
The main purpose of this study is to investigate and gauge the influence of rating websites and social media on consumers' purchasing behaviour and their choices. The present research considers a comparison between choosing a university and a restaurant by consumers based on using social media and online reviews. The study develops a multidimensional model to recognise the influence of online rating websites and social medial on consumer purchasing decisions. Results reveal that information adoption and risk-taking are important factors towards consumer purchasing decisions. However, there is no significant relationship between demographic traits and consumer purchasing decisions based on the proposed model and findings. Moreover, the study confirms that long-term benefits outweigh the expediency of a decision when respondents were reviewing websites.